2020
DOI: 10.3892/etm.2020.9032
|View full text |Cite
|
Sign up to set email alerts
|

Are objective ‘findings’ the same as subjective ‘severity’? A study of the relationship between computed tomography findings and subjective severity in preoperative CRSwNP patients

Abstract: In pre-surgical patients with chronic rhinosinusitis with nasal polyps (CRSwNPs), positive findings on computed tomography (CT) scans and an exacerbation of symptoms are two possible factors that indicate surgery. However, the relationship between these factors remains unclear. Confirmed CRSwNP patients ready for sinus surgery were consecutively enrolled. The Sino-Nasal Outcome Test 22 (SNOT-22) and visual analog scale (VAS) scoring were completed by these patients, and scores were subjected to factor analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Possible associations between the aforementioned CRSwNPs types and any single sinonasal sub-site involved (maxillary, ethmoid, frontal, or sphenoid) and OMC at CT scan were also evaluated. It was preferred to analyze the role of the CT staging system in relation to clinical and prognostic objective aspects of CRSwNPs instead of considering subjective symptomatological aspects as recently done by other authors [ 15 , 16 ]. The possibility of using preoperative partial CT scores as an additional instrument to stratify CRSwNP sub-types is nowadays worthy of investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Possible associations between the aforementioned CRSwNPs types and any single sinonasal sub-site involved (maxillary, ethmoid, frontal, or sphenoid) and OMC at CT scan were also evaluated. It was preferred to analyze the role of the CT staging system in relation to clinical and prognostic objective aspects of CRSwNPs instead of considering subjective symptomatological aspects as recently done by other authors [ 15 , 16 ]. The possibility of using preoperative partial CT scores as an additional instrument to stratify CRSwNP sub-types is nowadays worthy of investigation.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, some studies reported a significant correlation between CT and symptom scores. Hanyu et al [ 37 ▪ ] demonstrated a positive correlation between nasal symptoms and loss of smell, as well as an inverse correlation between pain and ocular symptoms, with objective radiological findings in patients with presurgical CRSwNP.…”
Section: The Role Of Conventional Radiography In Chronic Rhinosinusitismentioning
confidence: 99%